Minimal Change in Modal Logic S5 - Aguilera-Ventura, Carlos; Ben-Naim, Jonathan; Herzig, Andreas (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
We extend belief revision theory from propositional logic to the modal logic S5. Our first contribution takes the form of three new postulates (M1-M3) that go beyond the AGM ones and capture the idea of minimal change in the presence of modalities. Concerning the construction of modal revision operations, we work with set pseudo-distances, i.e., distances between sets of points that may violate the triangle-inequality. Our second contribution is the identification of three axioms (A3-A5) that go beyond the standard axioms of metrics. Loosely speaking, our main result states the following: if a pseudo-distance satisfies certain axioms, then the induced revision operation satisfies (M1-M3). We investigate three pseudo-distances from the literature (Dhaus, Dinj, Dsum), and the three induced revision operations (*Haus, *Inj, *Sum). Using our main result, we show that only *Sum satisfies (M1-M3) all together. As a last contribution, we revisit a major criticism of AGM operations, namely that the revisions of (p ∧ q) and (p ∧ (p → q)) are identical. We show that the problem disappears if instead of material implication we use the modal operator of strict implication that can be defined in S5.